The association between social support and chemotherapy-related toxicity in older patients with cancer. Issue 2 (March 2020) - Shahrokni, Armin; Sun, Can-Lan; Tew, William P.; Mohile, Supriya Gupta; Ma, Huiyan; Owusu, Cynthia; Klepin, Heidi D.; Gross, Cary Philip; Lichtman, Stuart M.; Gajra, Ajeet; Katheria, Vani; Cohen, Harvey Jay; et al.
Abstract: Objectives: The goal of this study was to evaluate the relationship between social support (SS) and grade 3–5 chemotherapy-related toxicities among older adults with cancer. Methods: This is a secondary analysis of a prospective longitudinal study of patients aged 65+ with solid cancer which led to the development of a predictive model for grade 3–5 chemotherapy-related toxicity (the Cancer and Aging Research Group [CARG] Chemotherapy Toxicity Risk Score). SS was measured by a modified version of Medical-Outcome Study-Social Support Survey and grade 3–5 hematological and non-hematological toxicities were captured and graded using CTCAE version 3.0. Patients were categorized into those with poor (SS score ≤ 75) and good SS (score of 76–100). Multivariate polychotomous logistic regression was used to examine the associations between SS and chemotherapy-related toxicity with adjustment for the CARG Toxicity Risk Score. Results: Compared to patients with good SS, those with poor SS were less likely to have grade 3–5 toxicity, especially for non-hematological toxicity (adjusted OR = 0.52, p  = .02). Patients who did not have someone to take them to the doctor "most" or "all of the time" were less likely to have grade 3–5 non-hematological toxicity compared to patients who had someone to take them to the doctor most or all of the time (adjusted OR = 0.32, p  = .02). Conclusion: Our study showed that patients with poor SS, especially those with less availability of someone to take them to doctors were less likely to have a documented grade 3–5 non-hematological toxicity.